Inovasi Produk, Promosi Sosmed Untuk Meningkatkan Target Konveksi Handayani Wirosari, Kab. Grobogan - Federius Ismanto; Martini; Nurrudin Mahmud (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this activity is so that business actors or SMEs can make good use of Social Media to support the marketing of tgeir Small and Medium Enterprise SME products and expand the reach of their target market or consumers through digital marketing. This is because the use of social media is considered more effective to reach all levels of society. Especially during the Covid-19 pandemic, people tend to spend more time on social media. This can be used by business actors to market their products online. With the large number of internet users, our team took the opportunity to suggest that SMEs in our service area market their products through social media and business actors can take advantage of the use of internet-based media properly and maximally to increase the marketing of the products they sell.The method in this service activity which is a solution to overcome partner problems is with assistance in the form of training using social media, human resource creativity, simple accounting for product design innovation. partner product sales. Simple accounting training is expected so that SME managers can separate business needs from personal needs.The results of this service are the realization of new product model design innovations, the existence of a business account that can be used as a tool for promotion, an understanding of the basics of accounting and the creativity of employees in managing SMEs